Another night life: the "Indie" city - Okeyo, Danielsun Ochieng (My University, 2011)
The aim of this project is to realize an urban and architectural space, as well as the architectural expression for a space of resistance and liberation particular the independent (‘Indie’) culture found within the city of Johannesburg. The project takes into account the principles of independent culture, the creative re-use of aged buildings and inner city regeneration to achieve a rationale for the deriving of an urban and architectural intervention. This is to be an intervention to generate and induce a vibrant nightlife within Johannesburg’s dormant inner city. The project investigates an alternative to the consumer nature of Johannesburg’s ‘society of the spectacle’, which has translated into consumer architecture and inner city decay. The extraction of ideals from a list of theorists and from architectural precedents, both current and historical (local and international), have been used to derive a rationale for design. In conjunction, practical considerations from the implementation of such an initiative have been considered. These considerations include, transport routes; the life stages of a nightclub intervention; the site selection processes; the immediate and existing urban environment and the existing night entertainment spaces. The result is a socially and economically feasible ‘night club space’ or spaces (derived from independent culture principals) where the individuals belonging to this independent culture can meet and interact. The execution of the project involves a re-thinking of night club space, as an integrated, post-work, post-Fordist, 24 hour space that goes beyond the notion of the generic nightclub, thus creating the opportunity for the architecture’s occupier to indulge in the unconventional in the quest for an experience independent from the regular. The resultant space becomes a catalyst for a new or renewed city identity.